ORIGINAL RESEARCH: IMAGING FEATURES IN A CASE OF WILSON'S DISEASE WITH DELAYED CLINICAL PRESENTATION - YAMUNA JAYASREE,; RUPESH MANDAVA, (International Journal of Pharma and Bio Sciences, 2016)
The aim of this article is to review and describe the ultrasound (US) and magnetic resonance imaging (MRI) features in Wilson's disease with a note on importance of early detection and treatment. Wilson's disease is an autosomal recessive disease which affects copper transport thereby resulting in copper accumulation in organs like brain, liver, cornea etc. Although prevalence of Wilson's disease is low, it is very important to promptly identify, diagnose and treat it as it is a treatable cause of liver disease. A 10 year old developmentally normal child presented with complaints similar to Wilson's disease. The clinical suspicion of Wilson’s disease was confirmed by the presence of the elevated value of 24 hour urinary copper after Dpenicillamine challenge test and with the help of imaging features. This patient also had hypersplenism.